Automatic Search of Threshold Implementations of 4‐Bit S‐Boxes Resisting DPA. Issue 1 (1st January 2017) - Liu, Bozhong; Gong, Zheng; Qiu, Weidong
Abstract : The threshold implementation method of Substitution box (S‐box) has been proposed by Nikova et al. for resisting first‐order Differential power attacks with glitches. To lower the time complexity for a threshold implementation of a specific non‐linear function, one needs to decompose the function first and then search possible share methods for it. However, the time complexity for this search process is still non‐trivial. In this paper, an effective method of searching threshold implementations of 4‐bit S‐boxes is proposed. It mainly consists of two stages. For the decomposing stage, an efficient way of decomposing an S‐box is introduced. For the sharing stage, the search complexity is lowered by the technique of time memory trade‐off. As a result, threshold implementations of various lightweight block ciphers' S‐boxes are given. Moreover, our method is applied to each 4‐bit involutive S‐box and some candidates of threshold implementations are presented.